The innovation gap of national innovation systems in the European Union - Edyta Dworak; Maria Magdalena Grzelak (Comparative Economic Research. Central and Eastern Europe, 2023)
The main aim of the paper is to assess the innovation gap between the national innovation systems (NIS) of the European Union (EU) and the average level of innovation of EU economies. The study takes into account NIS identified in the literature, i.e., (a) developed systems and (b) developing systems. In the theoretical part of the paper, the literature in the fields of NIS and the innovation gap is reviewed, the definitions and selected classifications of NIS around the world are presented, and the concept of the innovation gap between countries is defined. In the empirical part, the level of innovation in EU economies is assessed using Hellwig's synthetic development indicator. In order to measure the level of innovation in individual NISs, arithmetic means of national values of the synthetic measure of development (innovation) are used. The innovation gap is calculated as the quotient between the level of innovation of individual NISs analyzed in the study and the average level of innovation in EU economies. The study covered 2010 and 2021. The paper formulates the following research hypothesis: the level of innovation in EU economies is determined by the type of NIS. Consequently, developing system countries are less innovative and, thus, are characterized by an innovation gap in relation to the EU average. The results of the study confirm the hypothesis. The relationship between the innovation level of the EU economies and the type of NIS, as well as the assessment of the innovation gap between the national innovation systems of the EU and the average level of innovation of the EU economies, constitute the value-added of the paper.
Keywords: O30; O31; O43; 330; innovation; innovativeness of an economy; national innovation system; innovation gap